STRATEGI PENINGKATAN PENERIMAAN RETRIBUSI ASET TETAP TANAH DI KABUPATEN LOMBOK BARAT - Hailuddin, Hailuddin; Kholbi, Imam; Paranata, Ade; Wardah, Sofiati (Elastisitas : Jurnal Ekonomi Pembangunan, 2019)
This research is about strategies to increase levies of fixed assets / land in West Lombok Regency, with the aim to find out strategies to increase levies from the management of fixed assets (land) in West Lombok Regency. The study is quantitative descriptive, using time series data for 6 years, 2012-2017. Besides using secondary data, it is also strengthened by primary data which is collected through library studies, documentation, interviews and questionnaires. Data analysis uses SWOT analysis by identifying internal factors to determine aspects of strengths and weaknesses, as well as external factors to determine aspects of opportunity and threats. The results showed that there were 9 strategies that could be used to increase revenue from user fees for land use, including utilizing scientific and technological advances, increasing the number and quality of human resources in managing levies, working with related parties, improving local government land certification, land inventory local government, increase land rental rates and improve supervision of land assets. The results of this study are expected to be followed up by the West Lombok Regional Government in order to increase revenue from the use of regional wealth that is getting better